Job Crafting and Teachers' Organizational Citizenship Behavior in Chinese Colleges: The Mediating Role of Meaningful Work - Fu , Maozheng; Huang, Jian-Hao (Journal of Ecohumanism, 2024)
This study examines how job crafting and meaningful work influence organizational citizenship behavior among college teachers in Shandong Province, China. A questionnaire survey was administered to 601 college teachers.After controlling for teachers' demographic information, job crafting is positively correlated with organizational citizenship behavior among teachers in colleges. Additionally, meaningful work partially mediates this relationship, suggesting that teachers who find their work meaningful are more likely to engage in behaviors that benefit the organization beyond their formal job responsibilities. This study discusses the research findings from the perspective of enhancing organizational citizenship behavior among college teachers in China.